A Science Mapping Of HR Digital Evolution - Abdurrahim Abdurrahim; Apriya Santi; Jumiati Jumiati (Enrichment : Journal of Management, 2026)
This study aims to systematically map the development and intellectual structure of research on HR Digital Evolution in order to address the problem of conceptual fragmentation and the limited holistic understanding of digital evolution in Human Resource Management (HRM). The study employs a science mapping approach based on a Systematic Literature Review (SLR) using the PRISMA method combined with bibliometric analysis. Data were obtained from the Scopus database, comprising 41 indexed articles published between 2008 and 2025 that are relevant to the topic of HR Digital Evolution. The analysis was conducted to identify publication trends, major thematic clusters, knowledge structures, and the evolutionary dynamics of digital HR research. The findings indicate that research on HR Digital Evolution has increased significantly over the past decade, particularly in the post-pandemic period, with a dominant focus on digital technology integration, HR analytics, artificial intelligence, digital competency development, and their linkages to sustainability and human-centered values. The results also reveal the limited explicit use of classical HRM theories, indicating a theoretical gap in contemporary digital HR literature. The implications of this study are both theoretical and practical, strengthening the position of HR Digital Evolution as an interdisciplinary domain that requires the integration of socio-technical and dynamic capability theories, while also providing strategic guidance for academics and practitioners in designing more focused, sustainable, and evidence-based HR digital transformation agendas.